The Relationship of Foot Care with the Incident of Diabetic Foot Ulcers in Diabetes Mellitus Patients - Astuti, Kharina Indira; Purwanti, Okti Sri (Indonesian Journal of Global Health Research, 2024)
Diabetes mellitus is a non-communicable disease which ranks 6th as a cause of death in developing countries. Diabetics are at risk of complications if blood glucose is not controlled. High glucose levels can damage the nerves, blood vessels and arteries leading to the heart. This condition causes an increased risk of heart attack, stroke, kidney failure, peripheral vascular disease and other complications. In severe cases, diabetes can cause blindness, amputation, and even death. Objective to determine the relationship between foot care and the incidence of diabetic ulcers in diabetes mellitus sufferers at RSUD Dr. Soehadi Prijonegoro Sragen. This research uses quantitative methods with a cross sectional approach. The population in this study were all diabetes mellitus sufferers at RSUD Dr. Soehadi Prijonegoro Sragen in January-November 2023 with a total of 1565 patients. The sample in this study consisted of 66 diabetes mellitus patients who were selected using a purposive sampling technique. Data collection was carried out using the Nottingham Assessment of Functional Footcare (NAFF) questionnaire and observation sheets. The data analysis test in this study used a univariate test and a bivariate test using the chi square test. The majority of diabetes mellitus sufferers who were respondents in this study were female with the majority aged > 60 years, had a high school education level and had suffered from diabetes mellitus for a period of between 6-10 years. The majority of diabetes mellitus sufferers who were respondents in this study experienced diabetic ulcers. The majority of respondents in this study had good foot care. There was a significant relationship between foot care and the incidence of diabetic ulcers in diabetes mellitus sufferers at Dr. Soehadi Prijonegoro Hospital, Sragen. with a p-value of 0.009 (P<0.05). There is a significant relationship between foot care and the incidence of diabetic ulcers in diabetes mellitus sufferers at Dr. Soehadi Prijonegoro Hospital, Sragen.